Study of determinants of the farm soybean prices in USA. - Franco Tanaka, Manuel Maria (The Graduate School, Ajou University, 2010)
The thesis investigates the potential for using the simpler, single-equation framework to simultaneous-equation for annual supply and demand analysis in order to clarify farm soybean prices determiners in U.S. The methodology developed goes from Ordinary Least Square (OLS) to Two-Stage-Least-Square (TSLS) analysis. The results showed that an OLS can suffer from simultaneity biases when it uses Stock-to-use Ratio (Goodwin, Schnepf and Dohlman, 2001), and a TSLS model can give consistent estimators. Moreover, this research showed that US Corn Prices, as well China？s soybean import and Argentina？s soybeans ending stocks have statistical significance since they are jointly determined with US farm soybean prices. Further studies should consider variables related with soybean industry, as trading of co-products made of soybeans, as well technological developments or even more variables representing demand patterns.
학위논문(석사)--아주대학교 국제대학원--국제경영학과,2010. 4